A population-based survey for disabling headaches in Greece: Prevalence, burden and treatment preferences. (June 2021) - Constantinidis, Theodoros S; Arvaniti, Chryssa; Fakas, Nikolaos; Rudolf, Jobst; Kouremenos, Evangelos; Giannouli, Ermioni; Mitsikostas, Dimos D
Objective: To estimate the prevalence, burden and current treatment of disabling primary headaches in a large sample of the Greek population aged 18–70 years old. Methods: This is an observational descriptive study, with cross-sectional design performed by quantitative computer-assisted telephone interviews, using a validated 37-item questionnaire for headaches. The prevalence, burden, and current treatment of primary headaches (ICHD-3) were recorded along with participants' treatment preferences. Results: Out of 10, 008 interviewed participants, 1197 (12.0%) reported headaches affecting performance. The annual prevalence of migraine was 8.1% (95% confidence interval, 7.6–8.7, corresponding to 0.6 million Greeks), of chronic migraine 1.0% (95% confidence interval, 0.8–1.2, corresponding to 0.1 million), and of tension-type headache 3.8% (95% confidence interval, 3.4–4.2, corresponding to 0.3 million). The participants with headaches reported 0.5 headache-induced lost workdays per month (corresponding to 5.8 million lost workdays annually) and reductions in performance on 2.8 workdays per month (corresponding to 30.9 million workdays annually). In all, 43.4% of headache participants felt bad/ashamed because of headaches and 21.9% sought professional treatment, most often from a private neurologist. 83.8% of headache participants had never taken pharmacological prophylaxis, and only 5.5% were currently under preventative treatment. For both prophylactic and acute treatment, headache participants prefer oral medication to injection or stimulation devices. Conclusion: More than 10% of the Greek adult population up to 70 years old experience disabling headaches, causing a dramatic work loss. More than 80% of these have never taken pharmacological prophylaxis. Thus, enriching the quality of life of people with headaches relies crucially on expanding awareness about headaches and their treatment.